Schaum's outline of microeconomics - Salvatore, Dominick. 4 0 16; 5 (New York : McGraw-Hill, 2006)
Presents microeconomics study tools for students, including overviews of course fundamentals such as consumer demand theory, costs of production, price and output under different conditions, and game theory; hundreds of practice problems; and nearly nine hundred solved problems.
Includes index.
Young Adult.
Keywords: 2 -- 0; 6; Microeconomics. -- 20; 20; 2